Plant protection guides for organic arable and vegetable crops a growers resource - Teulon, D.A.J.; Cameron, P.J.; Bourdot, G.W.; Curtin, D.; Ralston, M. (New Zealand Plant Protection, 2004)
A New Zealand guide for pest, disease and weed management in organic arable andvegetable crops was developed. This guide is a resource for current organic growers andtheir consultants, as well as those contemplating converting to organics. It includesinformation collected from a wide range of sources within New Zealand and overseas.The guide has three parts: (I) a general section on the principles of soil, pest and diseaseand weed management in organic systems, (II) an arable section covering barley, borage,clover seed, grass seed, lentils, linseed, maize and wheat, and (III) a vegetable sectioncovering asparagus, brassicas, capsicum, carrot, onion, peas, potato, squash and tomato.For each crop there is a summary of the main pests, diseases and weeds to identify thepotential risks to organic growing. The options for preventing or managing these risksthat are available to organic growers given the cropping operations and control alternativesavailable to them are then described. This guide aims to fill the current gap between“introductory” and “anecdotal” organic publications with comprehensive documentationof growing operations that have been used successfully in specific crops for organicpest, disease and weed management.